PAJAK NEGARA DAN PAJAK DAERAH - Dini Vientiany; Najwa Nabila; Tasya Nadilla; Vany Fadillah Bastian (Kampus Akademik Publiser, 2024)
Indonesia has a major source of government revenue: the tax system. As per the present Constitution of the Republic Indonesia, tax is an obligation in social life as all levels of society are obliged to contribute to the state. Tax payments to the state are free of charge because the proceeds of the tax payments are used for state purposes to ensure the walfare and economic well being of the Indonesian populace. Indonesia's tax system is regulated by tax laws that aim to control the dynamic relationship involving the government and the individual/ entity taxpayer.